The Improving of the Student’s Vocabulary Achievement through Crossword Game in the New Normal Era - Bella, Yolanda Dita; Rahayu, Endang Mastuti (research, training and philanthropy institution Natural Aceh, 2023)
This research attempted to verify improved vocabulary achievement using the Crossword Game for the eleventh-grade students of SMAN 1 Krian. The method used was classroom action research. The reason why this research was done is because of the pre–cycle outcome. Only five students passed the criteria of minimum score (KKM). So, the researcher wanted to give fun vocabulary learning through Crossword Games. This research was done in 3 cycles. And the subject was one class of eleventh-grade students, which was a class that consisted of 28 students. The instruments were observation, tests, and questionnaires. According to the data analysis, the second cycle's scores are higher than the first. From 17% in pre–test to 75% in post–test 1, it meant that there was an improvement about 58%. Post-test 2, the students passed 85%. Observation showed that students became more engaged when crossword games were used, and their activities dominated the learning process. As much as 92% of students gave a positive opinion about crossword games that said crossword was fun, engaging, and easy for students to study vocabulary. Therefore, teaching the English language using crossword puzzle games could improve the students' vocabulary achievement.